2013
DOI: 10.2298/ciceq120407076r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrodynamics on kinetics of gluconic acid enzymatic production in bubble column reactor

Abstract: Oxidation of glucose by homogeneous glucose oxidase was performed in rectangular bubble column reactor at 40°C, ambient pressure and pH of 5.5 while superficial gas (oxygen) velocity was varied in the homogeneous and transition regime in the range of 0.0014 - 0.0112 m s-1. Effect of superficial gas (oxygen) velocity on the apparent reaction rate and its parameters was determined and it was observed that the apparent reaction rate on the basis of volume of the liquid increased with increasing the superfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The production of gluconic acid and relevant salts is one of the most important outcomes of the GOX‐catalyzed reaction. In pharmaceutical industries, sodium, calcium, zinc, and iron salts of gluconic acid are utilized to synthesize some well‐known drugs, such as Na, Ca, or Fe glucono‐delta‐lactone gluconates with various pharmaceutical applications 36,37 . For example, calcium gluconates are used to treat Ca‐associated deficiencies 36 .…”
Section: Gox Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of gluconic acid and relevant salts is one of the most important outcomes of the GOX‐catalyzed reaction. In pharmaceutical industries, sodium, calcium, zinc, and iron salts of gluconic acid are utilized to synthesize some well‐known drugs, such as Na, Ca, or Fe glucono‐delta‐lactone gluconates with various pharmaceutical applications 36,37 . For example, calcium gluconates are used to treat Ca‐associated deficiencies 36 .…”
Section: Gox Applicationsmentioning
confidence: 99%
“…Moreover, Ramezani et al. evaluated the impact of relevant hydrodynamic characteristics on kinetic parameters to reach more excellent GOX‐dependent gluconic acid production 18,37 . The process of glucose oxidation is also used as a medical diagnostic tool to measure the levels of blood glucose 38…”
Section: Gox Applicationsmentioning
confidence: 99%
“…GOD use is also an alternative way to production of H2O2 for textile bleaching (Tzanov et al 2002, Farooq et al 2013, Reis et al 2017, Qui et al 2017 or milk processing (Zhou &Lim 2009, Cruz et al 2013, Cruz et al 2012, Szweda et al 2013, Batista et al 2015. There are several studies about gluconic acid or gluconate salt production by GOD (Huang et al 2019, Han et al 2018, Ramezani et al 2013, Mariam et al 2010, Arimatsu et al 2004, Bao et al 2003, Shah & Kothari, 1993. GOD has analytical application to determine glucose levels of blood, serum, fruit juice etc., and it is also the most used enzyme in preparation of glucose biosensors (Ozyilmaz et al 2018, Khun et al 2012, Guo et al 2011, Salimi & Noorbahsh, 2011, Mazeiko et al 2013, Ozyilmaz et al 2007, Uang & Chou, 2003, Ekiz et al 2011, Wang et al 2013).…”
Section: Figure 1 Reaction Mechanism Of Godmentioning
confidence: 99%
“…As the volume of NaOH spent is proportional to the gluconic acid concentration, GOD activity is calculated as µmol gluconic acid.min -1 . There are several studies in which GOD activity was determined by monitoring gluconic acid concentration (Casolaro & Barbuccu, 1991, Bhat et al 2013, Iturbe et al 1989, Ramezani et al 2013, Yang et al 2004, Cui et al2019, Zhao et al 2002.…”
Section: Following the Gluconic Acid Productionmentioning
confidence: 99%
“…Several studies have been conducted to optimize the production of GA. For example, Purane et al ( 2011 ) optimized parameters such as glucose concentration, inoculum density and inoculum age for GA production using P. chrysogenum 724 and found that the maximum amount of GA produced (31.16 g/L) was reported at a glucose concentration of 100 g/L. Ping et al ( 2016 ) demonstrated the effects of oxygen supply on intracellular flux distribution for enhanced production of sodium gluconate by A. niger and reported that the higher oxygen concentration was required for enhanced synthesis of GA. Further, Ramezani et al ( 2013 ) reported the effects of hydrodynamic properties on kinetics parameters to achieve higher GA production by using GOD. It was found that the increased oxygen gas velocity resulted in the increasing rate of glucose oxidation reaction because of the higher transformation of oxygen from a gas to a liquid state.…”
Section: Applications Of God In Various Sectorsmentioning
confidence: 99%